116k views
0 votes
If f(x) =3^x+10 g(x) =4x -2 find (f-g)(x)
Help please greatly appreciated

1 Answer

7 votes

Answer:


(f-g)(x)=3^x-4x+12

Explanation:

The notation "(f-g)(x)" means we subtract the function g(x) from f(x) and get the expression. Very simple.

Let's do this:


f(x) =3^x+10

and


g(x) =4x -2

Now,


(f-g)(x)=[3^x+10]-[4x-2]\\(f-g)(x)=3^x +10 -4x + 2\\(f-g)(x)=3^x-4x+12

THis is the expression for (f-g)(x).

User Alex Wood
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.